Safety and reactogenicity of a liquid formulation of human rotavirus vaccine (porcine circovirus-free): A phase III, observer-blind, randomized, multi-country study. Issue 14 (25th March 2022) - Lau, Yu-Lung; Fan Leung, Ting; Sirvan Cetin, Benhur; Cagri Dinleyici, Ener; Huang, Li-Min; Halperin, Scott A.; Hsiao, Chien-Chou; Tapiero, Bruce; Tipton, Mary; Campbell, James D.; Moerman, Leentje; Povey, Michael; et al.
Graphical abstract: Highlights: The reactogenicity and safety of a liquid PCV-free HRV were assessed. Adverse event rates were similar for the liquid PCV-free HRV and the lyophilized HRV. In both groups, about 6% of infants reported at least one serious adverse event. The liquid PCV-free HRV has a favorable safety profile. Abstract: Background: The introduction of rotavirus vaccines in national immunization programs has decreased mortality and hospitalizations due to diarrhea. GSK's live-attenuated, human rotavirus vaccine (HRV) is a 2-dose vaccine for oral administration. Following the detection of porcine circovirus type 1 (PCV-1) in HRV, a PCV-free (no detection of PCV-1 and PCV-2 according to the detection limits of tests used) HRV was developed. The immunogenicity, reactogenicity and safety of a liquid (liq) PCV-free HRV were assessed in two prior studies. The present study aimed to generate additional reactogenicity and safety data. Methods: This phase III, observer-blind, randomized, controlled multi-country study enrolled healthy 6–12-week-old infants. Infants were randomized to receive 2 doses of either the liq PCV-free HRV (N = 677) or the lyophilized (lyo) HRV (N = 674) 1–2 months apart. Solicited adverse events (AEs) were recorded for 8 days after each dose, unsolicited AEs for 31 days and serious AEs (SAEs) from dose 1 until the end of the 6-month safety follow-up. Results: The occurrence of solicited general AEs was comparable between the liq PCV-free HRV and the lyo HRV groups, with irritability/fussiness being the most frequently reported (74.9% [95% confidence interval: 71.4–78.1] and 72.1% [68.6–75.5]). Unsolicited AEs were reported for 29.7% (26.3–33.3) and 30.6% (27.1–34.2) of infants in the liq PCV-free HRV and the lyo HRV group. A total of 39 and 38 infants reported at least one SAE, respectively. The most common SAEs were upper respiratory tract (0.7% and 0.9%) and urinary tract infections (0.9% and 0.6%). One SAE (constipation) in the liq PCV-free HRV group was considered as potentially causally related to vaccination by the investigator. No deaths were reported. Conclusions: The study showed that the reactogenicity and safety profiles of the liq PCV-free HRV and the lyo HRV are similar. ClinicalTrials.gov identifier: NCT03954743.